Menggugah Semangat Nasionalisme Melalui Penguatan Nasionalisme Pancasila di SMK Negeri 3 Palangka Raya - Muhammad Zusanri Batubara; Hendro T.G Samosir; Murniyati Yanur; Mahmuddin Sirait; Osi Karina Saragih; Nurlia Eka Damayanti; John Budiman Bancin; Windi Susetyo Ningrum (LPPM UNIVERSITAS DIAN NUSWANTORO, 2023)
The fading of nationalism is a real threat to Indonesia, especially the younger generation. The flow of modernization has an impact on the weakening of the spirit of nationalism of the younger generation and considers nationalism as a mere formality. Weakening nationalism can be a trigger for national destruction if it cannot be prevented wisely. This service activity aims to foster the spirit of nationalism through strengthening Pancasila nationalism to students of SMKN 3 Palangka Raya. This activity was carried out using a persuasive approach method in lectures, discussions, and question. The results of the activities carried out showed an increase in students' understanding of Pancasila nationalism. The students showed high interest in participating in the service activities. The high interest of the students can be seen from their enthusiasm in listening to the material as well as when interacting in discussion and question. The challenge of future activities is to carry out further activities so that the spirit of nationalism is even stronger.